Pengaruh OPT berdasarkan Suku bunga dan Jumlah Uang Yang Berdar Terhadap Inflasi Di Indonesia tahun 2018-2023 - Lita Desiana Fitri; andi hasrun; Mariam Kaliandan; Mindo Mursalina Jen (At-Thariqah: Jurnal Ekonomi, 2024)
Open market operations are a way for banks to control money in circulation by selling or buying government securities. OPT is closely related to the amount of money in circulation and interest rates. The purpose of this study is to determine the effect of open market operations based on interest rates and the amount of money in circulation on inflation in Indonesia from 2018 to 2023. The object of this study is quantitative. The data taken is secondary data by obtaining information through the official website of Bank Indonesia and the Central Statistics Agency. The results obtained are that interest rates and the amount of money in circulation have no effect on the amount of money in circulation. This can be seen from the t-test stating that the interest rate has a t-statistic value of 0.893 with a significance value of 0.438 and the amount of money in circulation has a t-statistic of 0.313 with a probability of significance of 0.775 which when compared to the degree of error or 5 percent.